Two Tumors, One Diagnosis: A Rare Case of Coexisting Secretory and Non-Secretory Paragangliomas - Rimsha Azhar, Mudasira Ishtiaq, Minahil Salam, Gohar Khan, Saira Bashir (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Paragangliomas (PGs) are a rare form of neuroendocrine tumors derived from neural crest cells. They are classified as parasympathetic, having symptoms of mass effect, or sympathetic, presenting with symptoms of catecholamine hypersecretion. In the majority of cases, a single benign lesion is encountered. The occurrence of multiple paragangliomas is a rare event discovered in only 1-2% of sporadic cases. Remarkably, in our case, the patient demonstrated coexisting lesions- a sympathetic paraganglioma in the para-aortic region and a parasympathetic in the para-glottic region. Only 70-85 cases of true laryngeal PGs have been reported in the literature, out of which 90% are supraglottic, making the para-glottic location exceedingly rare. Case presentation: We report the case of a 30-year-old female, initially presented with right submandibular neck swelling and symptoms of dyspnea, hoarseness of voice, snoring, daytime somnolence, sweating, and apprehension. She was diagnosed with a rare non-secretory right para-glottic paraganglioma, which was surgically excised. Months later, recurrent symptoms led to further evaluation, revealing a functionally active para-aortic paraganglioma, confirmed biochemically and histopathologically. 6 weeks post op, the symptoms regressed, and the patient is currently on follow-up. Discussion: When a paraganglioma is identified, it is crucial to screen for additional tumors. This approach is underscored by several key considerations drawn from the literature. Advanced imaging techniques, including functional imaging with DOTA PET scans, have proven effective in detecting multifocal disease and its management. Approximately 30-40% of paragangliomas and pheochromocytomas are associated with germline mutations. Identifying these mutations can have significant implications not only for the patient but also for family members who may be at risk. In resource-limited settings, the challenges of accessing advanced diagnostic tools and genetic testing are significant. Enhancing the availability of these resources is essential to optimizing patient care. Despite these challenges, the principles of thorough screening and vigilant follow-up remain applicable. Conclusion: Concurrent paragangliomas at abdominal and para-glottic sites are exceptionally rare. All cases of unexplained sympathetic overactivity should be screened biochemically for paraganglioma. Improved access to genetic counseling and testing is critical for optimal management and risk stratification. Long-term follow-up remains essential, even after symptom resolution.